Association Between Midlife Physical Activity and Incident Kidney Disease: The Atherosclerosis Risk in Communities (ARIC) Study - Parvathaneni, Kaushik; Surapaneni, Aditya; Ballew, Shoshana H; Palta, Priya; Rebholz, Casey M; Selvin, Elizabeth; Coresh, Josef; Grams, Morgan E (American journal of kidney diseases, 2021)
Physical activity is associated with lower risk for cardiovascular disease, diabetes, and hypertension, which have shared risk factor profiles with chronic kidney disease (CKD). However, there are conflicting findings regarding the relationship between physical activity and CKD. The objective was to evaluate the association between physical activity and CKD development over long-term follow-up using the Atherosclerosis Risk in Communities (ARIC) Study. Prospective cohort study. 14,537 participants aged 45 to 64 years. Baseline physical activity status was assessed using the modified Baecke Physical Activity Questionnaire at visit 1 (1987-1989) and categorized according to the 2018 Physical Activity Guidelines for Americans to group participants as inactive, insufficiently active, active, and highly active. Incident CKD defined as estimated glomerular filtration rate (eGFR)<60mL/min/1.73m at follow-up and≥25% decline in eGFR relative to baseline, CKD-related hospitalization or death, or initiation of kidney replacement therapy. Cox proportional hazards regression. At baseline, 37.8%, 24.2%, 22.7%, and 15.3% of participants were classified as inactive, insufficiently active, active, and highly active, respectively. During a median follow-up of 24 years, 33.2% of participants developed CKD. After adjusting for age, sex, race-center, education, smoking status, diet quality, diabetes, coronary heart disease, hypertension, antihypertensive medication, body mass index, and baseline eGFR, higher categories of physical activity were associated with lower risk for CKD compared with the inactive group (HRs for insufficiently active, 0.95 [95% CI, 0.88-1.02]; active, 0.93 [95% CI, 0.86-1.01]; highly active, 0.89 [95% CI, 0.81-0.97]; P for trend = 0.007). Observational design and self-reported physical activity that was based on leisure time activity only. Due to low numbers, participants who were not Black or White were excluded. Highly active participants had lower risk for developing CKD compared with inactive participants.